2011
DOI: 10.12681/mms.43
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Neural Networks (ANNs) for Weight Predictions of Blue Crabs (Callinectes sapidus RATHBUN, 1896) Using Predictor Variables

Abstract: An evaluation of the performance of artificial networks (ANNs) to estimate the weights of blue crab (Callinectes sapidus) catches in Yumurtalık Cove (Iskenderun Bay) that uses measured predictor variables is presented, including carapace width (CW), sex (male, female and female with eggs), and sampling month. Blue crabs (n=410) were collected each month between 15 September 1996 and 15 May 1998. Sex, CW, and sampling month were used and specified in the input layer of the network. The weights of the blue crabs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…This pattern was also observed in saltmarshes in the USA during high tides (Fitz & Wiegert, 1991). Previous studies reported higher blue crab growth and No data (Bilen et al, 2011) density in vegetated habitats compared to non-vegetated habitats (Lipcius et al, 2005;Perkins-Visser et al, 1996;Thomas et al, 1990) with an increase in survival rates in closely fragmented environments (Mizerek et al, 2011).…”
Section: Discussionsupporting
confidence: 56%
“…This pattern was also observed in saltmarshes in the USA during high tides (Fitz & Wiegert, 1991). Previous studies reported higher blue crab growth and No data (Bilen et al, 2011) density in vegetated habitats compared to non-vegetated habitats (Lipcius et al, 2005;Perkins-Visser et al, 1996;Thomas et al, 1990) with an increase in survival rates in closely fragmented environments (Mizerek et al, 2011).…”
Section: Discussionsupporting
confidence: 56%
“…However, the relationship between length and weight is often non-linear (Froese 2006), and transformations using linear regression methods may lead to low predictive values. In such cases, traditional statistical analysis methods, especially single or multiple linear regression models, may be limited in terms of quantification and prediction (Suryanarayana et al 2008, Türeli Bilen et al 2011, Benzer et al 2017, Benzer and Benzer 2019, Benzer and Benzer 2022.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies on predictive modeling using neural networks for the growth of aquatic organisms, specifically focusing on fish (Benzer and Benzer 2016, Benzer and Benzer 2017, Özcan and Serdar 2018, Özcan and Serdar 2019, Özcan 2019, Benzer and Benzer 2020, Benzer and Benzer 2023b, Akkan et al 2024) and crayfish (Türeli Bilen et al 2011, Benzer et al 2015, Benzer and Benzer 2018, Benzer and Benzer 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Since ANNs have a nonlinear structure, they perform better than traditional methods in terms of performance criteria. They can detect nonlinear relationships without any hypothesis (Hyun et al, 2005;Türeli Bilen et al;Benzer and Benzer, 2016;Benzer and Benzer, 2017;Özcan and Serdar, 2018;Özcan and Serdar, 2019;Özcan, 2019;Benzer, 2020;Benzer and Benzer, 2020a;Benzer and Benzer, 2020b).…”
Section: Introductionmentioning
confidence: 99%